Handbook of LGBT-affirmative couple and family therapy - Bigner, Jerry J.; Wetchler, Joseph L. (New York : Routledge, 2012)
"The editors and contributors of this comprehensive text provide a unique and important contribution to LGBT clinical literature. Spanning 30 chapters, they discuss the diverse and complex issues involved in LGBT couple and family therapy. In almost 15 years, this book provides the first in-depth overview of the best practices for therapists and those in training who wish to work effectively with LGBT clients, couples, and families need to know, and is only the second of its kind in the history of the field"--Provided by publisher.
LGBTQ couple and family therapy : history and future directions / Shawn V. Giammattei, Robert-Jay Green -- Gay male couple therapy: an attachment-based model / Gil Tunnell -- Lesbian couple therapy / Colleen M. Connolly -- Affirmative bisexual couple therapy / Mary Bradford -- Can couples change gender? couple therapy with transgender people and their partners / Jean Malpas -- Sex therapy for gay male couples: affirming strengths and stemming challenges / Philip A. Rutter -- Sex therapy with lesbian couples / Marla Cobin, Michele Angello -- Trans-sexual desire in differently gendered bodies / Arlene Istar Lev, Shannon Sennott -- Coming out to family: adrift in a sea of potential meanings / Valory Mitchell -- Working with LGBT families / Fiona Tasker, Maeve Malley -- The kids may be all right, but some might still end up in your office : working with children of LGBTQ parents / Katherine Kuvalanka -- Raising lesbian, gay, bisexual youth : an affirmative family therapy approach / Linda Stone Fish, Rebecca G. Harvey -- Supporting transgender youth and their families in therapy : facing challenges and harnessing strengths / Deborah Coolhart -- Considerations for assessment and intervention with lesbian and gay adoptive parents and their children / Mark Gianino, Michelle Novelle -- The gay and lesbian stepfamily : past and present research and implications for therapy / Jean Lynch, Kathy McMahon-Klosterman -- Counseling lesbian and gay individuals, couples, and families in late life / John A. Blando -- Helping heterosexual spouses cope when their husbands or wives come out / Carol Grever -- Intercultural issues in LGBTQQ couple and family therapy / Anneliese A. Singh, Amney Harper -- Issues in the health of lesbian, gay, bisexual, and transgender people for LGBT couple and family therapy / Thomas O. Blank, Marysol Asencio, Lara Descartes -- Spirituality and religion in same-sex couples' therapy / Sharon Scales Rostosky, Steven D. Johnson, Ellen D.B. Riggle -- Treatment of partner violence in gay and lesbian relationships / Deanna Linville, Krista Chronister, Mary Marsiglio, Tiffany B. Brown -- Treatment of substance use disorders in LGBT couples and families / Sandra C. Anderson -- LGBT couple enrichment / Shoshana D. Kereswky -- Therapeutic considerations in same-sex divorce / Kevin P. Lyness -- LGB-affirmative training strategies for couple and family therapist faculty : preparing heterosexual students to work with LGB clients / Thomas Stone Carlson, Christi R. McGeorge -- Queer supervision / Janie K. Long, Jack Grote -- Ethical issues in LGBT couple and family therapy / Damien W. Riggs -- Research on reorientation therapy / Julianne M. Serovich, Erika L. Grafsky, Rashmi Gangamma -- Helping individuals and families recover from sexual orientation change efforts and heterosexism / Jeff Lutes, Marsh McDonough -- A little bit pregnant? the ethics of same-sex marriage / Corinne Reczek, Esther Rothblum.
Keywords: Family psychotherapy; Marital psychotherapy; Couples -- Psychology; Sexual minorities -- Mental health; PSYCHOLOGY -- Psychotherapy -- Couples & Family; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family